PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XI SMA NEGERI 16 PADANG - Azhari, Regita Putri (Departemen Matematika, 2024)
Proficiency in mathematical problem solving is very important for students, as it is considered the main goal in mathematics education. However, this ability in grade XI at SMA Negeri 16 Padang seems to be lacking due to the absence of learning activities that encourage student engagement. The Two Stay Two Stray cooperative model was suggested to address this challenge. The impact of the TSTS model was investigated in this study. Non-equivalent Posttest Only Control Group Design pseudo-experiment was used in this study. The t-test showed a P-value <0.003, indicating that the TSTS learning model outperformed conventional learning in developing mathematical problem solving skills in class XI SMA Negeri 16 Padang.Keywords– Two Stay Two Stray, Mathematical Problem Solving Ability